Extranodal Marginal Zone B Cell Lymphoma of the Orbit In a Patient with Sarcoidosis: A Case Report - Richards, Nikisha; Kidwell, Earl; Ramadan, Ali; Naab, Tammy (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Objective: To describe a case of extranodal marginal zone B-cell lymphoma (EMZL) “mucosa associated lymphoid tissue (MALT)” of the orbit that presented with stage IV disease in a patient with sarcoidosis. Design: Clinicopathologic case report. Methods: Biopsies of the lesion were performed in the operating room and the samples were submitted for pathology processing. Pathology analysis identified the lesion as an extranodal marginal zone B-cell lymphoma “mucosa associated lymphoid tissue (MALT)” via flow cytometry, histopathology, cytogenetics, and immunohistochemical staining and fluorescent in situ hybridization (FISH). The institutional review board of Howard University Hospital waived the need for IRB approval for this intraoperative finding. Results: A 70-year-old Black woman with biopsy-proven sarcoidosis presented complaining of foreign body sensation, redness, swelling of her left upper eyelid and tearing. The patient was found to have an orbital lymphoproliferative malignancy. Conclusions: It is still unclear if the presence of immunosuppression or an autoimmune disease increases the risk of lymphoproliferative malignancies 6. Malignancy should always be suspected and investigated